The Influence of Disabilities in Activities of Daily Living on Successful Aging: The Role of Well-Being and Residence Location - Li, Xiaoshan; Wang, Jingjing; Dong, Shenghong; Fu, Jianping; Liu, Jianping (Frontiers in Public Health, 2020)
This study aimed to investigate the effect of disability in activities of daily living (ADLs) on successful aging, and the possible moderators between them. Based on data from the Chinese Longitudinal Healthy Longevity Surveys (CLHLS), we used the Cox proportional hazards model of survival analysis and multivariate regression analysis (SPSS 16.0) to test our hypotheses. Mortality or cognition impairment were the dependents variables, and disability in ADLs was the independent variable. Well-being and residence location were the moderators. The results showed that in survey 2005, the Chinese elders with disability in ADLs, after controlling elder's gender, age, residence place, and marital status, often experienced more mortality and cognition impairment risk in the next 3 years. Our findings also showed that the increased mortality risk among elders with disability in ADLs was lower in those with higher well-being or younger age. The increased cognitive impairment risk among elders with disability in ADLs was lower in those living in the city than those living in a rural area or small towns. These findings contribute to a better understanding of the relationship between disability in ADLs and successful aging among Chinese elders. Our findings also expose other elements to consider such as psychological factors (e.g., well-being) and residence location in the relationships between the disability in ADLs and mortality (or cognition impairment), which have a psychological impact in successful aging of the Chinese elders.